2012
DOI: 10.1158/1541-7786.mcr-11-0615
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibition of mTORC1 Kinase Activates Smads 1 and 5 but Not Smad8 in Human Prostate Cancer Cells, Mediating Cytostatic Response to Rapamycin

Abstract: Although hyper-activated mTOR is well recognized as being pivotal to prostate cancer growth and progression, the underlying mechanisms by which it promotes such responses remain incompletely understood. Here we show that rapamycin activates Smads 1 and 5 in human prostate cancer cells and tissues through blocking mTORC1 kinase. ShRNA-based gene silencing and gene overexpression approaches reveal that Smads 1 and 5 mediate while Smad8 represses rapamycin-induced cell death and expression of the BMP transcriptio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 50 publications
3
10
0
Order By: Relevance
“…The molecular mechanism behind suppression of BMP signaling by TGF-β is under investigation in our group. Our results that sh-mTOR and sh-Raptor activate Smad1/5/8 are consistent with our recent article demonstrating that mTORC1 kinase represses P-Smad1/5, whereas mTORC2 activates P-Smad1/5 in human PCa cell lines [63]. Despite the activation of BMP Smad signaling, Survivin levels remain elevated.…”
Section: Discussionsupporting
confidence: 93%
“…The molecular mechanism behind suppression of BMP signaling by TGF-β is under investigation in our group. Our results that sh-mTOR and sh-Raptor activate Smad1/5/8 are consistent with our recent article demonstrating that mTORC1 kinase represses P-Smad1/5, whereas mTORC2 activates P-Smad1/5 in human PCa cell lines [63]. Despite the activation of BMP Smad signaling, Survivin levels remain elevated.…”
Section: Discussionsupporting
confidence: 93%
“…Potential molecular mechanism may be explained that upregulated YB-1 contributed to reduced intracellular androgen accumulation, thus weaning PCa off androgen dependency and upregulating tumor survival [23]. In accordance with the present study, SMAD1 is reported to be signi cantly elevated in patients with high-risk PCa [24]. The same conclusion is also drawn by increasing evidence which show the downregulation of SMAD1 contributed to the PCa proliferation, migration and invasion [25].…”
Section: Discussionsupporting
confidence: 91%
“…It has been reported that rapamycin treatment activates the BMP-Smad pathway (van der Poel, Hanrahan, Zhong, & Simons, 2003;Wahdan-Alaswad et al, 2012) due to the dissociation of FKBP12 from the BMP type 1 receptor (Wang et al, 1996). Previous studies have alluded to the differential impact of rapamycin on mTORC1 and Akt signaling and rapamycin's contributions to apoptosis and cell survival.…”
Section: Increase In Mtor Signaling From Birth Does Not Rescue Bmp-mentioning
confidence: 99%